A genetic variant rs13293512 in the promoter of let-7 is associated with an increased risk of breast cancer in Chinese women. Issue 5 (24th May 2019) - Sun, Ruifen; Gong, Jianyu; Li, Ju; Ruan, Zhiguo; Yang, Xiaomi; Zheng, Yongren; Qing, Lili; He, Xiaoshan; Jiang, Jike; Peng, Yanxia; Zou, Haijian
Abstract : Growing evidence has demonstrated that single-nucleotide polymorphisms (SNPs) in the promoter of miRNA may influence individuals' susceptibility to human diseases. We examined two SNPs rs10877887 and rs13293512 in the promoters of let-7 family to determine if the two SNPs were related to the occurrence of breast cancer (BC). Genotyping of the two SNPs was performed by PCR and restriction fragment length polymorphism analysis or TaqMan assay in 301 BC patients and 310 age matched controls. We found a higher frequency of rs13293512 CC genotype and rs13293512 C allele amongst BC patients (CC vs TT: adjusted odds ratio (OR) = 1.78; 95% CI: 1.14–2.80; P =0.012; C vs T: adjusted OR = 1.33; 95% CI: 1.06–1.67; P= 0.013). Stratification analysis showed that rs13293512 CC genotype was associated with an increased risk of BC in patients with negative estrogen receptor (adjusted OR = 2.39; 95% CI: 1.32–4.30; P= 0.004), patients with negative progesterone receptor (adjusted OR = 1.92; 95% CI: 1.11–3.33; P= 0.02), patients with T1-2 stage cancer (adjusted OR = 1.77; 95% CI: 1.07–2.93; P= 0.03), and patients with N1-3 stage cancer (adjusted OR = 1.89; 95% CI: 1.13–3.17; P= 0.015). These findings suggest that rs13293512 in the promoter of let-7a-1/let-7f-1/let-7d cluster may be a possible biomarker for the development of BC in Chinese women.